Short-duration ischemic preconditioning does not improve jump or change of direction performance in elite male handball players - Okan Kamiş; Neslihan Akçay; Kadir Keskin; Nicholas Rolnick; Carlos García Sánchez; Victor S. de Queiros; Fatih Harun Turhan; João Guilherme Vieira; Alexander Montoye; Rodrigo Ramalho Aniceto (PLoS ONE, 2025)
This study aimed to compare the effects of a short-duration ischemic preconditioning (IPC) protocol with different cuff pressures on change of direction and jumping performance in elite male handball players. Twelve national-level male handball players (age:20.08 ± 3.12 years; height:1.81 ± 0.07 m; weight:77.88 ± 13.01 kg) participated in the study. Players visited the laboratory on five non-consecutive days. Following the familiarization session, each player completed four identical visits save for the cuff pressure used; cuff pressure was randomized into sham, 80% arterial occlusion pressure (AOP),100%AOP or 120% AOP with one used in each of the 2nd-5th visits. In the supine position, players underwent 3 cycles of 2 minutes of applied pressure and 2 minutes of reperfusion (total duration: 12 minutes). Ten minutes afterward, squat jumps (SJ) and countermovement jumps (CMJ) were performed in sequential order (5-minute rest between tests). Five minutes later, T-test and Zigzag test were performed (5-minute rest between tests). There was no significant difference across the IPC protocols for any of the parameters evaluated in the tests: SJ (F = 1.89; p = 0.151; ηp2 = 0.146), CMJ (F = 1.40; p = 0.260; ηp2 = 0.113), T-agility test (F = 0.01; p = 0.997; ηp2 = 0.002) and Zigzag test (F = 0.240; p = 0.860; ηp2 = 0.021). Our study found no effects of a 3x2-min IPC protocol using different IPC pressures on vertical jump and change of direction in elite male handball players. Therefore, it is premature to recommend the use of short-duration IPC protocols as a pre-exercise strategy for improving neuromuscular performance during ballistic and reactive athletic tasks in elite male handball players.